Technical and vocational education and training: proceedings... (Asian Development Bank ManilaPH, 1991)
Covers five broad themes viz. philosophy, rationale and systems of technical and vocational educational training (TVET); planning of TVET; financing of TVET; and policies and strategies for the development of TVET. Also looks at the role of international agencies in the development of TVET in developing countries.
DC